Regio- and Stereoselective (SN2) N-, O-, C- and S-Alkylation Using Trialkyl Phosphates - Banerjee, Amit; Hattori, Tomohiro; Yamamoto, Hisashi (Synthesis, 2021)
Bimolecular nucleophilic substitution (SN2) is one of the most well-known fundamental reactions in organic chemistry to generate new molecules from two molecules. In principle, a nucleophile attacks from the back side of an alkylating agent having a suitable leaving group, most commonly a halide. However, alkyl halides are expensive, very harmful, toxic and not so stable, which makes them problematic for laboratory use. In contrast, trialkyl phosphates are inexpensive, readily accessible and stable at room temperature, under air, and are easy to handle, but rarely used as alkylating agents in organic synthesis. Here, we describe a mild, straightforward and powerful method for nucleophilic alkylation of various N-, O-, C- and S-nucleophiles using readily available trialkyl phosphates. The reaction proceeds smoothly in excellent yield, and quantitative yield in many cases, and covers a wide range of substrates. Further, the rare stereoselective transfer of secondary alkyl groups has been achieved with inversion of configuration of chiral centers (up to 98% ee).
Keywords: trialkyl phosphates; stereoselectivity; SN2 reaction; amides; secondary alkylation; vinyl ethers